Cosmetic Serum Loaded Arabica Coffee (Coffea arabica) Extract: Formulation and Antioxidant Study - Harum Nadyanti Usman; Liza Pratiwi; Bambang Wijianto (Faculty of Pharmacy, Universitas Gadjah Mada, 2023)
Arabica coffee (Coffea arabica) is a natural antioxidant that can be used in the prevention of skin aging. This study was conducted to determine the comparison of variations in the composition of HPMC, CMC-Na, and Carbomer in the optimum formula of arabica coffee serum, then to determine the physical properties of the preparation, as well as the IC50 value ofarabica coffee extract and arabica coffee serum in the DPPH test. Arabica coffee extract was obtained by maceration method using 70% ethanol. Determination of the optimum formula of arabica coffee serum using the Simplex Lattice Design method. The optimum formula of arabica coffee serum was evaluated for physical properties including organoleptic test, homogeneity test, pH test, spreadability test, and adhesion test. The antioxidant activity of arabica coffee extract and the optimum formula of arabica coffee serum was tested using the DPPH method. Data analysis used SPSS One sample T-test statistics. The results showed that the composition variation of HPMC, CMC-Na, and Carbomer in the optimum formula of arabica coffee serum using the Simplex Lattice Design method was 0.1%:0.8%:0.1%. The resulting predicted values are a pH value of 4.88 and a spreadability value of 7.95 cm. The optimum formula of arabica coffee serum has the physical properties of the preparation, namely brown color, coffee aroma, light texture, a cool sensation when applied to the skin, homogeneous, has a spreadability of 7.93 cm, stickiness of 1 second, and pH value of 4.9. The IC50 value of arabica coffee extract and the optimum formula of arabica coffee serum are 8.13 ppm and 250 ppm. The results of the SPSS One sample T-test statistical analysis showed that there was no significant difference between the prediction response and the results of the optimum formula evaluation.